COVID-19 AND HEPATIC DYSFUNCTION- A PROSPECTIVE STUDY ON THE SEVERITY OF THE DISEASE - Nayan, Santosh Kumar; Kumar, Santosh; Kumar, Abhay; Dev, Anand; Singh, Siddharth (Student’s Journal of Health Research Africa, 2024)
Background A patient who died due to respiratory failure suffering from COVID-19 revealed severe liver injuries in the postmortem. This indicated that the virus starts affecting other organs of the body simultaneously with the respiratory system. Around 23% of the patients who suffered due to COVID-19 had liver injuries. This study has been conducted to determine the relationship between liver injuries with COVID-19 and also to determine the severity of COVID-19 when liver injuries are reported. Method This was a cross-sectional study conducted prospectively to determine the correlation between liver dysfunction and the severity of COVID-19. The study was carried out for 6 months at IGIMS, Patna in Bihar, India. 150 patients above the age of 18 years suffering from COVID-19 were considered for this study. Liver function tests and tests for inflammatory markers were carried out and the patients were monitored thoroughly during hospitalization and one month later. Results 95 patients among the 150 had severe COVID and the remaining 55 had moderate COVID-19. The patients who had moderate COVID-19 infection had around 80% survival rate whereas the patients with severe COVID-19 infection had a 30% survival rate. The non-survivors and those with severe COVID-19 had a higher occurrence of liver dysfunction. Also, it was found that liver enzymes had a substantial association with the presence of inflammatory markers. Conclusion This study reported higher levels of liver enzymes in the patients infected with COVID-19 indicating its association. Overall liver dysfunction was prominent among the non-survivors and those who had severe COVID-19. Also, a significant relationship was derived between inflammatory markers and the occurrence of liver dysfunction. Recommendation Doctors should monitor inflammatory markers and liver function as well to check the prognosis of the disease in elderly individuals suffering from COVID-19.